Potencial de inóculo para patogenicidade de Macrophomina Phaseolina (tassi) goid. em meloeiro - Nascimento, Luan Vítor (Universidade Federal Rural do Semi-Árido, 2018)
Root rot-causing pathogens are considered a major threat for muskmelon production in the Brazil’s main producing areas. Macrophomina phaseolina is within the most incident fungi in the producing regions of Rio Grande do Norte and Ceará states and hard to control. The pursuit for resistant accessions and varieties, as well as alternative control methods for this fungi is a continuous task. To reliably evaluate control methods we need pathogenic isolates, efficient inoculation methods and inoculum potential that is capable of causing infection in the plant. This way, the present study aimed to assess the ideal inoculum potential to cause root rot in muskmelon. Two trials were carried out in greenhouse, one using rice as inoculum-substrate for M. phaseolina, and another one using a sandy-organic substrate, both conducted in a completely randomized experimental design, with six treatments referring to the inoculum potential (0, 9, 18, 27, 36, and 45 g per L of substrate) and six replicates. Disease incidence and severity were evaluated 30 days after planting. The inoculum potential of 18 g.L-1, in rice and sandy-organic substrate, was efficient in promoting root rot in muskmelon, and may be indicated for use in studies that requires soil infestation.
Monografia
Keywords: Cucumis melo; Fungos habitantes do solo; Podridão radicular; Cucumis melo; Soilborne pathogens; Root rot; CIENCIAS AGRARIAS::AGRONOMIA